Automatic detection of early gastric cancer in endoscopy based on Mask region-based convolutional neural networks (Mask R-CNN)(with video) - Jin, Jing; Zhang, Qianqian; Dong, Bill; Ma, Tao; Mei, Xuecan; Wang, Xi; Song, Shaofang; Peng, Jie; Wu, Aijiu; Dong, Lanfang; Kong, Derun (Frontiers in Oncology, 2022)
The artificial intelligence (AI)-assisted endoscopic detection of early gastric cancer (EGC) has been preliminarily developed. The currently used algorithms still exhibit limitations of large calculation and low-precision expression. The present study aimed to develop an endoscopic automatic detection system in EGC based on a mask region-based convolutional neural network (Mask-RCNN) and to evaluate the performance in controlled trials. For this purpose, a total of 4,471 white light images (WLIs) and 2,662 narrow band images (NBIs) of EGC were obtained for training and testing. In total, 10 of the WLIs (videos) were obtained prospectively to examine the performance of the RCNN system. Furthermore, 400 WLIs were randomly selected for comparison between the RCNN system and doctors. The evaluation criteria included accuracy, sensitivity, specificity, positive predictive value and negative predictive value. The results revealed that there were no significant differences between the pathological diagnosis with the RCNN system in the WLI test (2=0.189, P=0.664; accuracy, 90.25%; sensitivity, 91.06%; specificity, 89.01%) and in the NBI test (2=0.063, P=0.802; accuracy, 95.12%; sensitivity, 97.59%). Among 10 WLI real-time videos, the speed of the test videos was up to 35 frames/sec, with an accuracy of 90.27%. In a controlled experiment of 400 WLIs, the sensitivity of the RCNN system was significantly higher than that of experts (2=7.059, P=0.000; 93.00% VS 80.20%), and the specificity was higher than that of the juniors (2=9.955, P=0.000, 82.67% VS 71.87%), and the overall accuracy rate was higher than that of the seniors (2=7.009, P=0.000, 85.25% VS 78.00%). On the whole, the present study demonstrates that the RCNN system exhibited an excellent performance status for the detection of EGC, particularly for the real-time analysis of WLIs. It may thus be effectively applied to clinical settings.